Quality of Life in People Living with HIV/AIDS attending ART Plus Centre in Kanpur Nagar - Dixit, Gopal Krishan; Nigam, Seema; Midha, Tanu (Indian Journal of Community Health, 2023)
Background: HIV/AIDS affects an individual physically as well as mentally, socially and financially. ART treatment has increased life expectancy so Quality of Life (QOL) has become an important aspect. Aim & Objective: To assess QOL in people living with HIV/AIDS attending ART Plus center in Kanpur Nagar. Material and Methods: A cross sectional study was carried out on 407 registered patients at ART Plus centre from 1st march 2021 to 31st December 2021.WHOQOL-HIV BREF instrument was used to assess Quality of life. Result: Overall QOL score of male patients (14.62±2.05) was found higher than female patients (13.46±1.92). Married study subjects had maximum overall QOL score (14.65±2.00) and minimum QOL score was found in Widowed (12.99±1.84). Maximum overall QOL score was found in Class I (15.62±2.08) and minimum score was found in Class V (13.60±2.00) of modified BG Prasad socioeconomic classification. The study showed that there was an association between QOL scores with gender, marital status and socioeconomic status. Conclusion: In this study QOL score was found higher in male, married study subjects with higher socioeconomic status.